Unemployment as the socio-economic effect against labour market turbulence - Kamba-Kibatshi, Marcel (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
Unemployment involves a lot of very negative impact on society of different effects. The economic impact in a number of positions on unemployment are always mentioned first. The macroeconomic effects of these involve drainage of public finance benefits and other social benefits for people affected by unemployment. This phenomenon, as already mentioned in the study involves the reduction of the state budget revenues, due to the lack of payment of the income taxes and unemployment insurance premiums. Work is in this context, a very important factor of production and mass unemployment is under-utilization of such an important factor for the economy. In addition, the obvious thing is that very often people who can not find employment are forced to emigrate or fatal to your work 'black'. Unemployment is a new phenomenon in the Polish society because arouses great controversy. In Poland, this phenomenon has appeared only in the 90.tych twentieth century with the start of the transition process. Change of regime change resulted not only in political, but also economic and not just in this country. Unemployment can have on society, the consequences of pathological. The causes of unemployment in developed Western countries have a different nature. It has its source primarily in the technological implementation of new technologies that replace human work while increasing productivity, as the high wages it pays to entrepreneurs. It's not easy to find an unambiguous definition of unemployment is acceptable to both the researchers, politicians and those involved in the practical aspects of this phenomenon and the effects generated by them. The reason for this is that the phenomenon with which we are dealing, sometimes referred to as a complex, multi-dimensional, "elude" cognition. It is difficult to point out the importance of directly relevant to the whole captured of unemployment, as well as the need to resort to conventional arrangements.

Bezrobocie pociąga za sobą bardzo wiele niekorzystnie wpływających na społeczeństwo różnych skutków. Skutki ekonomiczne w wielu publikacjach na temat bezrobocia zawsze wymieniane są jako pierwsze. W skali makroekonomicznej skutki te pociągają za sobą drenaż finansów publicznych na zasiłki i inne świadczenia socjalne dla osób dotkniętych bezrobociem. Zjawisko to, jak już wspomniano w opracowaniu, pociąga za sobą również zmniejszenie dochodów budżetowych państwa, ze względu na brak płacenia przez bezrobotnych podatków dochodowych i składek ubezpieczeniowych. Praca jest w tym kontekście bardzo ważnym czynnikiem produkcji a masowe bezrobocie oznacza niepełne wykorzystanie tego, tak ważnego dla gospodarki czynnika. Ponadto, oczywistą rzeczą jest to, że bardzo często osoby, które nie mogą znaleźć zatrudnienia zmuszone są do emigracji zarobkowej lub zgubnej dla państwa pracy „na czarno”. Bezrobocie jest zjawiskiem nowym w polskim społeczeństwie, dlatego wzbudza ogromne kontrowersje. W Polsce zjawisko to pojawiło się dopiero w latach 90. XX wieku wraz z rozpoczęciem procesów transformacji ustrojowej. Zmiana ustroju spowodowała nie tylko zmiany polityczne, ale przede wszystkim gospodarcze i to nie tylko w tym kraju. Bezrobocie może mieć dla społeczeństwa również konsekwencje patologiczne. Przyczyny bezrobocia w rozwiniętych krajach zachodnich mają inną naturę. Ma ono swe źródło przede wszystkim w postępie technicznym, wprowadzaniu nowych technologii, które zastępują pracę ludzką podnosząc jednocześnie wydajność pracy, co przy wysokich płacach opłaca się przedsiębiorcom. Wcale nie jest łatwo znaleźć niedwuznaczną definicję bezrobocia, możliwą do zaakceptowania zarówno przez badaczy, polityków, jak i osoby zajmujące się praktycznymi aspektami tego zjawiska i generowanymi przez nie skutkami. Przyczyną takiej sytuacji jest to, że zjawisko, z jakim mamy tu do czynienia, bywa określane jako złożone, wielowymiarowe, „wymykające się” poznaniu. Trudno wskazać na znaczenia bezpośrednio odnoszące się do całościowo ujmowanego zjawiska bezrobocia, jak również trzeba odwoływać się do ustaleń konwencjonalnych.